An overview of cancer immunotherapeutic strategies. (27th August 2018) - Wahid, Braira; Ali, Amjad; Rafique, Shazia; Waqar, Muhammad; Wasim, Muhammad; Wahid, Khansa; Idrees, Muhammad
Artificially boosting body's immune response is one of the most exciting, effective and promising advancements in the treatment of cancers. Cancer immunotherapeutics consist of variety of treatment approaches such as cytokine therapy, adoptive T-cell transfer therapy, and antibodies that stimulate innate and adoptive immune responses. In addition to this, development of HPV vaccine has paved way toward the development of other cancer vaccines. Checkpoint blockade inhibitors, for example, anti-programmed cell death protein 1 and anti-cytotoxic T-lymphocyte-associated antigen-4, chimeric antigen receptor T-cell therapy and monoclonal antibodies are emerging as other major breakthroughs that are highly effective against cancer. This review addresses the current status of immunotherapeutic strategies against cancer and provides baseline data for future research.